Identification of chemically modified peptide from poly(D,L-lactide-co-glycolide) microspheres under in vitro release conditions - Murty, Santos B. (Springer-Verlag, 2003)
The purpose of this research was to study the chemical reactivity of a somatostatin analogue octreotide acetate, formulated in microspheres with polymers of varying molecular weight and co-monomer ratio under in vitro testing conditions. Poly(D,L-lactide-co-glycolide) (PLGA) and poly(D,L-lactide) (PLA) microspheres were prepared by a solvent extraction/evaporation method. The microspheres were characterized for drug load, impurity content, and particle size. Further, the microspheres were subjected to in vitro release testing in acetate buffer (pH 4.0) and phosphate buffered saline (PBS) (pH 7.2). In acetate buffer, 3 microsphere batches composed of low molecular weight PLGA 50∶50, PLGA 85∶15, and PLA polymers (≤10 kDa) showed 100% release with minimal impurity formation (<10%). The high molecular weight PLGA 50∶50 microspheres (28 kDa) displayed only 70% cumulative release in acetate buffer with significant impurity formation (∼24%). In PBS (pH 7.4), on the other hand, only 50% release was observed with the same low molecular weight batches (PLGA 50∶50, PLGA 85∶15, and PLA) with higher percentages of hydrophobic impurity formation (ie, 40%, 26%, and 10%, respectively). In addition, in PBS, the high molecular weight PLGA 50∶50 microspheres showed only 20% drug release with ∼60% mean impurity content. The chemically modified peptide impurities inside microspheres were structurally confirmed through Fourier transform-mass spectrometry (FT-MS) and liquid chromatography/mass spectrometry (LC-MS/MS) analyses after extraction procedures. The adduct compounds were identified as covalently modified conjugates of octreotide with lactic and glycolic acid monomers within polymeric microspheres. The data suggest that due to steric hindrance factors, polymers with greater lactide content were less amenable to the formation of adduct impurities compared with PLGA 50∶50 copolymers.